2013
DOI: 10.1088/0960-1317/23/6/065026
|View full text |Cite
|
Sign up to set email alerts
|

Development of a thermopile infrared sensor using stacked double polycrystalline silicon layers based on the CMOS process

Abstract: A stacked double-layer (SDL) thermopile-based infrared sensor, which comprised of 96 thermocouples on a suspended membrane, has been designed and fabricated with a CMOS-compatible process. The thermoelectric properties were characterized, and responsivity (R s) of 202.8 V W −1 and detectivity (D *) of 2.85 * 10 8 cm Hz 1/2 W −1 for a SDL thermopile were derived.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 48 publications
0
37
0
Order By: Relevance
“…Since the Seebeck coefficient of poly-Si varies with the temperature of the device and the micro-heater will inevitably affect the temperature of the device, it is crucial to make sure that the temperature rise caused by the micro-heater will be minimized and not affect the performance of the thermopile too much. Our previous work [42] shows that the output voltage at different temperatures is linear with the applied input power. Therefore it can be concluded that the testing results of the test key are still reasonable.…”
Section: A Design Of Thermopilementioning
confidence: 93%
See 4 more Smart Citations
“…Since the Seebeck coefficient of poly-Si varies with the temperature of the device and the micro-heater will inevitably affect the temperature of the device, it is crucial to make sure that the temperature rise caused by the micro-heater will be minimized and not affect the performance of the thermopile too much. Our previous work [42] shows that the output voltage at different temperatures is linear with the applied input power. Therefore it can be concluded that the testing results of the test key are still reasonable.…”
Section: A Design Of Thermopilementioning
confidence: 93%
“…The detailed analysis is shown in our previous work [42]. Another significant parameter, D * is defined as:…”
Section: A Design Of Thermopilementioning
confidence: 99%
See 3 more Smart Citations